Analisis Pengaruh Gaya Kepemimpinan dan Motivasi terhadap Kinerja Karyawan Departemen Penjualan Di PT Sumbermulia Hasilguna Jakarta - Lwanga Tindra Matutino Kinarsih, Carolus (Journal of Economics & Business UBS, 2020)
The research aims to examine and analyze the influence of leadership style and motivation toward performance of employee in PT Sumbermulia Hasilguna Jakarta. Data collected through distribution of questionnaires and it is implemented to PT Sumbermulia Hasilguna Jakarta’s 58 employee. Analysisof data in this research using the help of SPSS version 20. A sampling technique usesa census method and data test technique is used within the research includes validity test by factor analysis, reliability test with cronbach. Classic assumption test anddouble linear regression analysis, to verify and to prove the research hypotheis. Analysis result demonstrates that leadership style don’t have a positive influence toward employee performance and motivation have a positive influence toward employee performance. However, based on the results of tests conducted by simultaneous test (F test) shows that overall free variable Leadership Style (X1) and Motivation (X2) together have a significant influence on Employee Performance. The value of R Square is 0.579, meaning that Leadership Style (X1) and Motivation (X2) are together able to explain Employee Performance variable equal to 57,9% while the rest equal to 42,1% are the variables not proposed in this research.